Investigating the Effects of Horizontal Transition with Student-Preferred Learning Materials in a Virtual Biology Laboratory - Asad Ullah Khan; Aftab Alam; Shah Khalid; Sehat Ullah; Fakhr ud Din (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2024)
Adaptive Virtual Learning Environments (VLEs) present customized teaching materials to individual students which help them to achieve their learning goals and serve quite a vital role in virtual learning environments. In this paper, we present a new student-centered learning approach in a three-dimensional (3D) virtual biology laboratory (VBIOLAB). The approach is based on the concept of horizontal transition with student preference (HTWSP) implemented with the help of VBIOLAB. The HTWSP is based on the concept of allowing students to choose their preferred learning styles according to their needs and pace instead of automatically adapted aids. HTWSP allows students to stay in a certain module and attain more information about that learning module through various aids of their choice. To go to the next learning module there is a mechanism of vertical transition which allows a student to make quick progress by skipping the details about a certain module. Intermediate-level students participated in experiments that compared the proposed system with an adaptive virtual laboratory. Experimental results indicated that 75% of students improved their examination scores through the use of VBIOLAB. Data from the system usability scale (SUS) and the subjective rating supported greater participation, motivation, and effectiveness in learning using VBIOLAB. The experimental results reveal that this approach is effective and vital to utilize to enhance students’ learning in 3D-VLEs.